Using Critical Thinking Technology in Teaching Idioms to University Students - Kurbanova Dilbar Aknazarovna (Researchparks Publishing, 2022)
We live in a world where technology exists everywhere. Due to the ubiquitous availability of technology, the teaching methodology has also undergone some changes. The phrase “electronic education” or “technology in education” has become a hype in every educational environment. The introduction of technology into education is really important because it satisfies the needs of today's students. Today's classroom environment is completely different from a traditional audience. Traditional methods, mainly based on lectures and teaching, are reduced to learning to remember English. In this article, opinions and comments will be made about the use of project-based approach in the teaching of Sciences in universities.